QUALITY CONTROL PARAMETERS OF VATARI GUGGULU- AN AYURVEDIC FORMULATION - Shalini, *Parashar; Prajapati, P.K.; Harisha, C.R; Pandya, D.H (International Journal of Ayurveda and Pharma Research, 2016)
Vatari Guggulu has been prepared according to Bhaishajya Ratnavali and is indicated in Amavata, Gridhrasi, Katishula etc. It is an example of Guggulu kalpa in Vati form which means medicines containing equal or more amount of Guggulu as compared to amount of other ingredients. Vatari Guggulu is prepared from Castor oil, Gandhaka (Processed Sulphur), Triphala (Haritaki, Bibhitaki and Amalaki) and Guggulu. The present study deals with development of pharmacognostical and preliminary pharmaceutico-analytical profile of Vatari Guggulu which is lacking. It revealed the pH [5% aqueous suspension] is 4.0, water-soluble extractive 29.1% w/w, alcohol-soluble extractive 41.84% w/w, carbon di sulphide extractive 22.76% w/w, petroleum ether soluble extractive 15.48% w/w, ash value 14.77% w/w and loss on drying [at 105°C] are 8.35%w/w. Physical tests revealed average weight of Vatari Guggulu vati is 376 mg and 7.51 mm diameter and has an average 2.18 kg/cm2 hardness, disintegration time 2 hr 45 min [in distilled water] and 0.00043% friability. High performance thin layer chromatography [HPTLC] of alcoholic extract of drug revealed 6 and 5 Rf values at 256 and 366 nm out of which only one Rf was similar among Rf values at either wavelength.